PELATIHAN BAHASA INGGRIS PADA ANAK SEKOLAH DASAR DAN ANAK USIA DINI DI DESA CIHIDEUNG - Rista, Mufidah, Nola Sriyola Anggraeni, Rihatul jannah (JURNAL PENGABDIAN KEPADA MASYARAKAT SERUMPUN MENCIPTA, 2024)
This research explores various effective learning methods to improve the English language skills of primary and early childhood children in Cihideung.By adopting a fun and interactive learning approach, the study aims to create a conducive learning environment for participants preferences for specific learning methods and their effect on learning motivation. The results of the study are expected to contribute to development of a more relevant and enganging English curriculum for children.